Deciphering the Role of Endolysosomal Ca2+ Channels in Immunity - Alharbi, Abeer F.; Parrington, John (Frontiers in Immunology, 2021)
The role of endolysosomal Ca2+ signalling in immunity has been a subject of increasing interest in recent years. Here, we discuss evolving knowledge relating to the contribution of endolysosomal Ca2+ channels that include TPCs, TRPMLs, and P2X4R in physiological processes related to innate and adaptive immunity—including phagocytosis, inflammation, cytokine/chemokine release, dendritic, natural killer, and T cell activation and migration—and we underscore the paucity of clinical studies in this field. Emerging biomedical and translational data have led to important new insights into the critical roles of these channels in immune cell function and the regulation of innate and adaptive immune responses. The evolving immunological significance of endolysosomal Ca2+ signalling warrants further investigations to better characterize the roles of these channels in immunity in order to expand our knowledge about the pathology of inflammatory and autoimmune diseases and develop endolysosomal Ca2+ channels as viable biomarkers and therapeutic and preventive targets for remodelling the immune response.